PENGEMBANGAN E-MODUL PADA MATERI NILAI-NILAI PANCASILA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS lV SEKOLAH DASAR - Cynthia, Devi; Kumala Sari, Cut; Ayudia, Inge (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is based on the learning of Pancasila Education in the material of Pancasila values, problems were found that still use package books, printed modules, and whiteboards as the main learning resources. Based on the results of observations and interviews, it is known that teachers have not used e-modules in the learning process so that learning is still teacher-centered, less interesting, and causes low student participation in understanding the material of Pancasila values. Therefore, the researcher developed an e-module as an interactive digital teaching material on Pancasila values in the lV grade of elementary school. The purpose of this study is to find out the development process, level of validity, and practicality of e-modules in the material of Pancasila values for Pancasila education subjects in class lV SD Negeri Sukarejo. This research uses the Research and Development (R&D) method with a 4D development model which includes the stages of Definite, Design, Development, and Disseminate. Data collection techniques are carried out through observation, interviews, questionnaires, and documentation. The results of the study show that the e-modules developed obtained the category of